Prevalence of Work-Related Musculoskeletal Symptoms in Veterinary Surgeons—A Cross-Sectional Survey - Kim, Sun Young; Yu, Denny; Simons, Micha C.; Breur, Gert J. (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objectives The aim of this study was to determine the prevalence of work-related musculoskeletal symptoms (MSS) in veterinary surgeons using an online survey.Study Design An online survey was distributed to 1,031 diplomates of American College of Veterinary Surgeons. Responses were collected with data regarding surgical activities, experience with various types of MSS in 10 different body sites and attempts to reduce MSS.Results Two hundred and twelve respondents (21% response rate) completed the distributed survey in 2021. Ninety-three per cent of respondents had experienced MSS associated with surgery in at least one body part, with the neck, lower back and upper back frequently affected. Musculoskeletal discomfort and pain worsened with prolonged surgical hours. Forty-two per cent of them suffered from chronic pain persisting longer than 24 hours after surgeries. Musculoskeletal discomfort was common regardless of practice emphasis and procedure types. Forty-nine per cent of respondents with musculoskeletal pain had taken medication, 34% sought physical therapy for MSS and 38% ignored the symptoms. Over 85% of respondents showed more than some concern regarding career longevity due to musculoskeletal pain.Clinical Significance Work-related MSS are common in veterinary surgeons, and the results of this study warrant longitudinal clinical studies to determine risk factors and attention to workplace ergonomics in veterinary surgery.
Keywords: veterinary surgeons; musculoskeletal symptoms; ergonomics